2014
DOI: 10.1007/s12639-014-0448-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Leishmania major DNA within wild caught Phlebotomus papatasi and species composition of sand flies in endemic focus of cutaneous leishmaniasis, in western Iran

Abstract: Cutaneous leishmaniasis is one of the most important public health problem in many developing countries. The present study was conducted to determine the vector(s), the parasite and the species composition of sand flies in the Dehloran County during May-November 2012. Sand flies were collected by sticky traps and mounted in Puri's medium for species identification. Polymerase chain reaction (PCR) techniques of kDNA, ITS1-rDNA, followed by restriction fragment length polymorphism (RFLP) were used for identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Investigations on the epidemiology of leishmaniasis and bioecology of sand flies are important factors for disease management and to plan control programmes [29,30]. However, the abundance of sand flies in a leishmaniasis endemic region is merely not sufficient to characterize them as vectors responsible for transmitting leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations on the epidemiology of leishmaniasis and bioecology of sand flies are important factors for disease management and to plan control programmes [29,30]. However, the abundance of sand flies in a leishmaniasis endemic region is merely not sufficient to characterize them as vectors responsible for transmitting leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the predominance of CL due to L. major has already been confirmed mainly in Khuzestan, Kermanshah, and Ilam in previous studies too. [ 11 12 ] These provinces are the closest ones to our study area, so the results could be overlapped together. There are some other studies on leishmaniasis in different neighborhood regions of Poldokhtar, but we have mentioned just the ones that are more similar to our investigation in goals, methods, and findings.…”
Section: Discussionmentioning
confidence: 99%
“…The results of his study have been indicated that P. papatasi is only species found infected by L. major and is the principal vector of the disease. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrate the use of a similar PCR-based assay as an effective form of surveillance in the detection of non-endemic P. papatasi sand flies. PCR-RFLP has been used extensively in regions where leishmaniasis is endemic as a means of identification for both sand fly [38,39,40,41,42] and Leishmania [27,28,29] species. In addition to PCR-RFLP, DNA barcoding [43,44,45,46,47] and matrix-assisted laser desorption/ionization time of flight mass spectrometry [48,49,50] have also been used to differentiate sand fly species.…”
Section: Discussionmentioning
confidence: 99%
“…Leishmania major is ingested by P. papatasi in its amastigote form, where it replicates and is later injected into a mammalian host as a promastigote [21]. Phlebotomus papatasi comprises either a majority or a significant portion of sand fly trap captures in the Middle East and Egypt [22,23,24,25,26], including Iran where CL is especially prevalent [27,28,29]. Currently, P. papatasi has not yet been found in the New World.…”
Section: Introductionmentioning
confidence: 99%